2022
DOI: 10.3389/fcvm.2022.936018
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin exercise in the treatment of hypertension: A systematic review and meta-analysis

Abstract: BackgroundAs a therapy to prevent and treat hypertension, exercise is widely used in clinical practice. But due to the lack of documentary evidence, Baduanjin as a relaxed and convenient mode of exercise is not currently recommended by professional health organizations to treat hypertension. The purpose of this article is to examine the efficacy of Baduanjin as an antihypertensive exercise therapy.MethodsOur systematic retrieved of the entire relevant literatures in 12 databases. Finally, 28 eligible trials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In summary, according to our study, 24-form is the most recommended for those older adults to prevent falls. We can conclude that as a moderate intensity aerobic exercise [ 51 ], 24-form is beneficial for muscle strength, balance, physical coordination, and postural stability for older adults. The United Nations (UN) General Assembly declared 2021–2030 the UN Decade of Healthy Ageing.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, according to our study, 24-form is the most recommended for those older adults to prevent falls. We can conclude that as a moderate intensity aerobic exercise [ 51 ], 24-form is beneficial for muscle strength, balance, physical coordination, and postural stability for older adults. The United Nations (UN) General Assembly declared 2021–2030 the UN Decade of Healthy Ageing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Another study confirmed that Baduanjin exercise would increase the oxidation of fat, increase the muscle weight, reduce the percentage of body fat, and prevent fat accumulation. [ 32 ] Qigong Baduanjin belongs to aerobic exercise, and its intensity and sequence of exercise conform to the laws of human kinematics, which is safe and reliable. [ 33 ] The characteristics of Baduanjin Movement are mainly embodied in the aspects of tenderness, the combination of movement and stillness, the combination of spirit and shape, and the existence of qi.…”
Section: Discussionmentioning
confidence: 99%
“…This may be associated with the high incidence of hypertension in the country and the low cost of exercise treatment ( 25 ). China follows closely in third place, which may also be credited to the high incidence of hypertension and the popularity of traditional Chinese practices such as Baduan Jin and Tai Chi ( 26 , 27 ). The top 10 institutions make up 21.85% of total publication yields, indicating significant academic accomplishments.…”
Section: Discussionmentioning
confidence: 99%